2015
DOI: 10.1016/j.socscimed.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unemployment on self-reported health and mental health in Greece from 2008 to 2013: A longitudinal study before and during the financial crisis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
272
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(290 citation statements)
references
References 46 publications
10
272
3
5
Order By: Relevance
“…This is consistent with Drydakis' study, which also shows that adverse health consequences of unemployment in Greece are greater among women. 12 Our results also suggest that 'austerity' had negative effects on the health of both men and women over and above the recession. Unlike the first cohort, among the second cohort there was a significant divergence between the employed and the unemployed, with the unemployed becoming much more likely to report poorer health.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This is consistent with Drydakis' study, which also shows that adverse health consequences of unemployment in Greece are greater among women. 12 Our results also suggest that 'austerity' had negative effects on the health of both men and women over and above the recession. Unlike the first cohort, among the second cohort there was a significant divergence between the employed and the unemployed, with the unemployed becoming much more likely to report poorer health.…”
Section: Discussionmentioning
confidence: 50%
“…Another study from Greece, by Drydakis, examined the periods 2008-2009 and 2010-2013 and found that, while unemployment was associated with worse health in both periods, the difference was greater in the second period, when unemployment was higher. 12 In that case, women were most affected. These contrasting findings on the role of gender reflect the wider literature, which also finds differences.…”
Section: Introductionmentioning
confidence: 94%
“…Swedish studies on somatic and psychological symptoms (Novo, Hammarströ m and Janlert, 2000) and mortality risk (Å hs and Westerling, 2006) among the unemployed did not find any noticeable variation with overall unemployment level. A Greek study even found worse health effects of being unemployed when unemployment is common (Drydakis, 2015), and a Canadian study could not confirm that effects of unemployment on health vary with unemployment rates (Beland, Birch and Stoddart, 2002). Noelke and Beckfield (2014) found increased mortality among older American workers who lost their jobs during recessions, while job loss in booming economic conditions was not associated with higher mortality.…”
Section: Previous Researchmentioning
confidence: 97%
“…Several scholars have examined the potential health consequences of a large-scale economic recession, such as the current downturn (see, among others, Reeves, Stuckler, McKee, Gunnel, Chang, & Basu, 2012;De Vogli, Marmot, & Stuckler, 2013;Drydakis, 2015). The hypothesis that the worsening economic climate might have negatively affected the psychological wellbeing of the labour force is in line with our general finding that the risks of reporting being in poor mental health were higher in 2013 than in 2005, especially among the unemployed.…”
mentioning
confidence: 99%